2022
DOI: 10.3390/ijms232415903
|View full text |Cite
|
Sign up to set email alerts
|

AKBA Promotes Axonal Regeneration via RhoA/Rictor to Repair Damaged Sciatic Nerve

Abstract: The existing studies by our team demonstrated the pro-recovery effect of 3-Acetyl-11-keto-beta-boswellic acid (AKBA) on a sciatic nerve injury. To further investigate the role of AKBA in peripheral nerve injury repair, The TMT quantitative proteomics technique was used to obtain differentially significant proteins in a Sham group, Model group, and AKBA group. After that, three time points (5, 14, and 28 d) and four groups (Sham + AKBA, Sham, Model, and AKBA) were set up, and immunoblotting, immunofluorescence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Schwann cells are most likely involved in endogenous repair after spinal cord injury 13 . Our previous studies have shown that AKBA can promote the expression of BDNF and NGF 24 . The results of this experiment show that AKBA promotes the migration of Schwann cells through the polarization of macrophages to M2, and secretes neurotrophic factors to promote the repair of spinal cord injuries.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Schwann cells are most likely involved in endogenous repair after spinal cord injury 13 . Our previous studies have shown that AKBA can promote the expression of BDNF and NGF 24 . The results of this experiment show that AKBA promotes the migration of Schwann cells through the polarization of macrophages to M2, and secretes neurotrophic factors to promote the repair of spinal cord injuries.…”
Section: Discussionmentioning
confidence: 60%
“… 13 Our previous studies have shown that AKBA can promote the expression of BDNF and NGF. 24 The results of this experiment show that AKBA promotes the migration of Schwann cells through the polarization of macrophages to M2, and secretes neurotrophic factors to promote the repair of spinal cord injuries. Therefore, AKBA not only reduces spinal cord injury by reducing inflammation but also promotes the migration of Schwann cells and facilitates the repair of spinal cord injury.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations